TRADITIONAL AND MODERN-CONTEMPORARY STYLES - Syafril Syafril; Amaruddin Amaruddin (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2022)
In general, the style of interpretation is conventionally classified into the periodization of the interpretation itself. Interpretation that appeared in the Middle Ages are identified with style of fiqh, kalam, philosophy, tasawuf. The interpretation that appeared in the modern-contemporary era often have the style of adabi ijtimai', ilmi, haraki, hidai. But in this paper, the style of interpretation is classified into traditional and modern-contemporary. This classification refers to the understanding of the style that developed in the history of Islamic thought. In general, Islamic thought is divided into two major streams, namely traditionalism and modernism. Both of these interpretations have their own paradigms. As in general scientific studies, intellectuals who study the Quran must use a paradigm when doing interpretation, because it is inherent in the theory of interpretation. It is used in the arranging the interpretation conciously or unconciouslys. The style of traditional interpretation can be seen in the three paradigms. The three paradigmatic theories are the technical paradigm, the accommodation paradigm, and the reductionist paradigm. Meanwhile, the modern-contemporary style of interpretation with functional paradigm theory, namely making the Qur'an as guidance or huda in all aspects of life and the literacy paradigm theory which makes the Qur'an the greatest book of literature. These two paradigms distinguish traditional and modern-contemporary interpretations.